Neuro science (Sinauer Associaltes, 2004)
Neuroscience is a comprehensive textbook created primarily for medical and premedical students. In a single concise and approachable volume, the text guides students through the challenges and excitement of this rapidly changing field. The length and accessibility of the writing are a successful combination that works equally well for medical students or for undergraduate neuroscience courses in which many of the students are premeds. Being both comprehensive and authoritative, the book is also appropriate for graduate and professional use. Key features of the Third Edition include: